Sister chromatid exchanges and chromosome aberrations in lymphocytes of nurses handling antineoplastic drugs - Goloni-Bertollo, E. M. [UNESP]; Tajara, E. H. [UNESP]; Manzato, A. J. [UNESP]; Varella-Garcia, M. (Wiley-Blackwell, 1992)
Chromosomal aberrations (CA) and sister-chromatid exchanges (SCE) were investigated in peripheral lymphocytes of 15 nurses and nurse's aides handling cytostatic agents in hospital oncology units. Significantly increased frequencies were noted for both CA and SCE rates when the exposed individuals were compared with 15 nurses working in other hospital units and to a control sample matched by sex and age. This points to the need for emphasizing protective measures in the handling of anti-neoplastic agents.
Keywords: Antineoplastic agent; Chromosome aberration; Clinical article; Controlled study; Female; Human; Human cell; Lymphocyte; Nurse; Priority journal; Side effect; Sister chromatid exchange; Adult; Antineoplastic Agents; Chromosome Aberrations; Female; Human; Nurses; Nurses' Aides; Occupational Exposure; Sister Chromatid Exchange; Support, Non-U.S. Gov't; Support, U.S. Gov't, P.H.S.